1518. Bacteremia due to Non-Staphylococcus aureus Gram-positive Cocci and Risk of Cardiovascular Implantable Devices Infection. (15th December 2022) - Chesdachai, Supavit; Baddour, Larry M; Sohail, Rizwan; Palraj, Raj; Madhavan, Malini; Tabaja, Hussam; Fida, Madiha; Lahr, Brian D; DeSimone, Daniel C
Abstract: Background: Cardiovascular implantable electronic devices (CIED) infection carries significant morbidity, mortality, and financial burden. Bacteremia in patients with CIED increases risk of CIED infection. While several investigations have examined Staphylococcus aureus bacteremia and risk of CIED infection, data regarding non- S. aureus gram-positive coccal (non-SA GPC) bacteremia in patients with CIED has been both limited and dated. The current study examined the clinical characteristics of patients with CIED who developed non-SA GPC bacteremia and their proclivity of CIED infection. Methods: We reviewed all patients with CIED who developed non-SA GPC bacteremia at Mayo Clinic between 2012–2019. Cases with a left ventricular assist device, non-hospitalization, and contaminated blood culture were excluded. The 2019 European Heart Rhythm Association International Consensus Document was used to define CIED infection. Results: A total of 160 patients with CIED developed non-SA GPC bacteremia during the period. Ninety (56.2%) patients had CIED infection, with 60 (37.5%) classified as definite and 30 (18.8%) possible. This included 41/64 (64.1%) patients with coagulase-negative Staphylococcus (CoNS), 30/41 (73.2%) patients with Enterococcus, 13/19 (68.4%) patients with viridans group streptococci (VGS), and 6/36 (16.6%) patients with other non-SA GPC. The odds of CIED infection (with 95% CI) for CoNS, Enterococcus, and VGS bacteremia were 8.9 (3.2–24.6), 13.6 (4.5–41.6), and 10.8 (2.9–40.0) -fold higher, respectively, as compared to other non-SA GPC. Among those with infected CIED, 51 (56.7%) patients underwent complete device extraction after a median of 6 (IQR 3.5–10) days. In an unadjusted analysis of patients with CIED infection, the reduction in one-year mortality following device removal was not statistically significant (HR 0.59, 95% CI 0.26–1.33, p=0.198). Conclusion: The overall prevalence of CIED infection following non-SA GPC bacteremia was higher than previously reported, particularly that due to CoNS, Enterococcus, and VGS. Further study with a larger cohort is needed to demonstrate the survival benefit from CIED extraction in patients with infected CIED due to non-SA GPC. Disclosures: Larry M. Baddour, M.D., Boston Scientific: Advisor/Consultant|Botanix Pharmaceuticals: Advisor/Consultant|Roivant Sciences: Advisor/Consultant|UpToDate, Inc.: Royalty payments - authorship duties Rizwan Sohail, M.D., Aziyo Biologics: Advisor/Consultant|Boston Scientific: Advisor/Consultant|Medtronic: Advisor/Consultant|Philips: Advisor/Consultant|Philips: Honoraria Malini Madhavan, M.B.B.S., Biosense Webster: Advisor/Consultant|Biotronik Inc: Advisor/Consultant|Boston Scientific: Grant/Research Support|Convatec: Advisor/Consultant.